A Comprehensive Review on the Manipulation of the Sphingolipid Pathway by Pathogenic Bacteria - Rolando, Monica; Buchrieser, Carmen (Frontiers in Cell and Developmental Biology, 2019)
Bacterial pathogens have developed many different strategies to hijack host cell responses to promote their own survival. The manipulation of lipid biogenesis and cell membrane stability is emerging as a key player in bacterial host cell control. Indeed, many bacterial pathogens such as Legionella, Pseudomonas, Neisseria, Staphylococci, Mycobacteria, Helicobacter or Clostridia are able to manipulate and use host sphingolipids during multiple steps of the infectious process. Sphingolipids have long been considered only as structural components of cell membranes, however, it is now well known that they are also intracellular and intercellular signaling molecules that play important roles in many eukaryotic cell functions as well as in orchestrating immune responses. Furthermore, they are important to eliminate invading pathogens and play a crucial role in infectious diseases. In this review, we focus on the different strategies employed by pathogenic bacteria to hijack the sphingolipid balance in the host cell to promote cellular colonization.